Enhanced anaerobic digestion of kitchen waste at different solids content by alkali pretreatment and bentonite addition: Methane production enhancement and microbial mechanism. (February 2023) - Hu, Yuying; Liu, Susu; Wang, Xiaofan; Zhang, Shihao; Hu, Tengfang; Wang, Xin; Wang, Chuqiao; Wu, Jing; Xu, Li; Xu, Gaoping; Hu, Fengping
Graphical abstract: Highlights: Alkali pretreatment/bentonite addition for kitchen waste AD were explored firstly. AP/Be treatment could enhance the methane yield by 236%. AP/Be treatment could enrich bacterial microbial diversity. Hydrogenotrophic methanogenesis Methanobacterium was promoted by AP/Be treatment. Methanogenic pathways shifted as TS increased. Abstract: High solid anaerobic digestion (AD) has been considered as a promising and sustainable technology for treating kitchen waste. To enhance AD of kitchen waste, alkali pretreatment and bentonite addition treatment (AP/Be) was performed on kitchen waste, and microbial community was investigated at different total solids (TS) content (10%, 13%, 19%, 22% and 25%). The results indicated that after AP/Be treatment, methane yield was as high as 198 mL CH4 /g volatile solid (VS), which increased by 236% as the control. Moreover, microbial community analysis revealed that AP/Be treatment enriched bacterial microbial diversity. At TS of 10%, AP/Be treatment enhanced the hydrogenotrophic methanogens ( Methanobacterium ) significantly. In addition, the dominant methanogenic pathways changed at different TS content. These results demonstrated AP/Be treatment had a positive effect on methanogenesis during kitchen waste anaerobic digestion process. This study threw new insights towards enhancing kitchen waste anaerobic digestion, as well as the microbial mechanism.